Dampak Pandemic Covid-19 dan Restrukturisasi terhadap Pertumbuhan Kredit di PT. Bank Negara Indonesia Tbk - Erlina Yulianti Pratiwi; Nining I; Soesilo Soesilo (STEKOM PRESS, 2024)
Directly or indirectly the covid-19 pandemic in Indonesia has an impact on the banking sector, especially in lending to the public and decreasing debtor credit ollectability. The purpose of this study is to analyze the impact of the covid-19 pandemic on credit growth at PT. Bank Negara Indonesia Tbk using Pool Data in the monthly period starting from January 2018 to December 2022 with the Ordinary Least Squere (OLS) method through the approach of collectability failure, credit period, credit interest rate, inflation, business location, covid pandemic period, credit restructuring period, and GRDP in 9 business sectors. This study proves that credit growth at PT Bank Negara Indonesia is negatively and significantly influenced by ollectability failure, credit period, credit.